Optimal Compensation in Competitive Labor Markets with Heterogeneous Employers and Workers - Samuel Häfner; Niklas Haeusle; Winfried Koeniger; Alexander Braun (Institute of Labor Economics (IZA), 2024)
We develop a model in which large risk-neutral firms and individual risk-averse consumers compete to employ heterogeneous workers by posting compensation menus. Production takes time, and we analyze how screening motives interact with the desire to smooth consumption. There is a unique symmetric separating equilibrium that is also efficient. In equilibrium, the extent to which the compensation scheme delays payment until the production quality becomes known depends on whether, and to which extent, the consumers are financially constrained. We discuss how our model relates to the design of compensation schemes in current online peer-to-peer markets.
Keywords: D15; D82; D86; E24; J33; M52; 330; adverse selection; self selection; peer-to-peer markets; labor markets; capital market imperfections